Constrained predictive control and its application to a coupled-tanks apparatus - Poulsen, N; Kouvaritakis, B; Cannon, M (2001)
The focus of this paper is the development and application to experimental equipment of fast constrained predictive control algorithms. A review of QP based algorithm and an alternative using interpolation and LP is considered. Despite its undemanding computational nature, the latter algorithm is found to perform well both in simulation and when applied to an actual coupled-tanks rig. The advantages of the algorithm are further illustrated by comparison with desaturated PID control.